Cerebral Small Vessel Disease Clinical, Neuropsychological, and Radiological Phenotypes, Histopathological Correlates, and Described Genotypes: A Review. (31st December 2015) - Issac, Thomas Gregor; Chandra, Sadandavalli Retnaswami; Christopher, Rita; Rajeswaran, Jamuna; Philip, Mariamma
Abstract : Introduction . Vascular cognitive impairment is a common yet preventable cause for dementia. It needs high degree of suspicion and appropriate designing of investigatory tools to confirm diagnosis, identify comorbidities, and ascertain the areas of impairment. Commonly DSM-IV criterion is applied for diagnosis and detailed clinical and neuropsychological examination for identifying the specific phenotype is used. Early diagnosis using the mandatory criteria will help in early initiation of disease modifying treatment strategies which can result in partial reversal of vascular changes and arrest of progression. Patients with young onset disease might require genetic characterization for designing more aggressive treatment. Discussion and Conclusion . Dementias as such carry poor course and prognosis resulting in severe Disability Adjusted Life Years (DALYs) for patients and caregivers. Therefore, it is mandatory to identify treatable and preventable causes so that man power loss can be reduced.